TIC y créditos ECTS: una combinación ineludible en la Enseñanza-Aprendizaje de Lenguas - Baynat Monreal, Mª Elena; Sanz Gil, Mercedes (Didáctica. Lengua y Literatura, 2007)
European Higher Education Area (EHEA) and the implementation of the new systems of credits ECTS (European Credit Transfer and Accumulation System) adapted from the perspective of a formative paradigm socio-constructivism focused on the students, demand of the professorship, the application of new educational methodologies, and of the students, the development of new processes learning. In this context, the functionalities that ICT can provide as way for the immediate access to all kinds of information and his process, as well as for the interpersonal communication, constitute at present an indispensable combination that will improve the process of these changes. In the present work we propose to indicate, on the one hand, the most important changes that are waited from teachers and learners in the process of programs placed in the European harmonization; and on the other hand, to highlight the benefits that the integration of certain technologies can contribute as a fundamental part of the development of the above mentioned programs. In these sense we take as example the utilization of a virtual platform of support to the teaching (Moodle) for the teaching and learning of the French language. La construction de l’Espace Européen de l’Éducation Supérieure (EEES) et les nouveaux systèmes de crédit ECTS (European Credit Transfer and Accumulation System/ Système Européen de Transfert et d’Accumulation de Crédits) mis en place depuis la perspective d’un nouveau paradigme formatif socioconstructiviste centré sur les apprenants, exigent des professeurs, l’application des nouvelles méthodologies d’enseignement, et des étudiants, le développement de nouvelles méthodes d’apprentissage. Dans ce contexte, les fonctionnalités que les TIC peuvent apporter comme moyen d’accès immédiat à toute sorte d’information, ainsi qu’à la communication interpersonnelle, constituent actuellement une combinaison fondamentale qui favorisera la mise en marche de ces changements. Nous nous proposons dans ce travail, d’une part, montrer les changements les plus importants qu’on attend de la part des professeurs et des étudiants lors de la mise en pratique des programmes encadrés dans l’Harmonisation Européenne; et d’autre part, souligner les bénéfices que l’intégration de certaines technologies peuvent apporter en tant que partie fondamentale du développement des programmes cités. Pour cela, nous prenons l’exemple de l’utilisation d’une plate-forme virtuelle d’appui à la éthodologie pratique (Moodle) pour l’enseignement-apprentissage de la langue française.